Market Orientation Of Male And Female Entrepreneurs: A Preliminary Study In Malaysia Halal Food Industry - Ida Rizyani, Tahir; Mazita, Mokhtar; Noor Azlinna, Azizan; Shariman, Mustafa (2013)
This paper examines the relationship between market orientation and firm performance for male and female entrepreneurs among small and medium firms in the Malaysia halal food industry. In this preliminary study, results indicate that market orientation had a positive impact on the sales growth of men and women-owned firms. The relationship was investigated using Pearson product-moment correlation coefficient. There was a weak, positive correlation between the two variables. An independent samples t-test was conducted to compare the market orientation scores for males and females. There was no significant difference in scores for males and females.